A comparative analysis and survival analysis of open versus minimally invasive radical antegrade modular pancreatosplenectomy for pancreatic cancer: a systematic review and meta-analysis - Zhou, Yating; Xue, Fei (Frontiers in Oncology, 2025)
BackgroundPancreatic ductal adenocarcinoma (PDAC) is a major public health concern, ranking as the fourth leading cause of cancer-related mortality in the United States. Traditional surgical approaches often yield suboptimal outcomes, highlighting the need for innovative surgical strategies. Radical antegrade modular pancreatosplenectomy (RAMPS) has demonstrated improvements in surgical visualization and oncological outcomes. Recently, laparoscopic RAMPS (L-RAMPS) has been introduced as a minimally invasive alternative.ObjectivesThis meta-analysis aims to compare the safety and efficacy of open RAMPS (O-RAMPS) versus L-RAMPS, focusing on operative outcomes, minimally invasive outcomes, intra-abdominal outcomes, overall postoperative outcomes, and oncologic outcomes.MethodsA systematic review and meta-analysis were conducted following PRISMA guidelines. Eligible studies included prospective or retrospective cohort studies and randomized controlled trials comparing L-RAMPS with O-RAMPS. Data were extracted from EMBASE, PubMed, and the Cochrane Library databases through September 16, 2023. The ROBINS-I tool was used to assess the risk of bias. Statistical analyses included odds ratios (OR), risk differences (RD), mean differences (MD), and survival analyses.ResultsEight studies involving 588 patients were included. O-RAMPS was associated with longer operative times (MD = 39.39 minutes, 95% CI = 22.93 to 55.84) and greater blood loss (MD = -231.84 mL, 95% CI = -312.00 to -151.69). No significant differences were observed in blood transfusion rates, pancreatic fistula rates, delayed gastric emptying, or length of hospital stay. L-RAMPS demonstrated a shorter time to oral feeding (MD = -0.79 days, 95% CI = -1.35 to -0.22). Survival analysis suggested a potentially improved long-term prognosis for L-RAMPS.ConclusionL-RAMPS offers advantages over O-RAMPS in terms of reduced blood loss, faster time to oral feeding, and potentially better long-term prognosis. Further research is warranted, particularly regarding the learning curve of L-RAMPS and its broader applicability.Systematic review registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD42024498383.